Regulating Traditional Chinese Medicine Practitioners and Acupuncturists in Ontario, Canada - Glen E. Randall; Mark G. Embrett; Neil G. Barr; Diana K. Vania (McMaster University Library Press, 2015)
In 2006, the Ontario government passed the Traditional Chinese Medicine Act, which granted Traditional Chinese Medicine practitioners and Acupuncturists (TCM/A practitioners) self-regulatory status under the Regulated Health Professions Act, 1991. The goal of the legislation was to create a new regulatory college that would set and enforce high standards of care and safety in order to enhance public protection and access to a range of traditional and alternative therapies. In April 2013, the College of Traditional Chinese Medicine Practitioners and Acupuncturists of Ontario was officially launched. Several factors account for the government's decision to delegate self-regulatory authority to TCM/A practitioners through the creation of a regulatory college. In particular, the government's decision seems to have been influenced by lobbying of some practitioners, greater public acceptance of alternative medicines, patient safety concerns related to acupuncture cases in the media, and the precedence of self-regulatory status being granted to these practitioners in other provinces. The degree to which the legislation has achieved its goals is difficult to determine given the short period of time the regulatory college has existed. However, the fact that the college has developed standards of practice to guide TCM/A practitioners and has a process in place to address public complaints is an early indication of movement toward achieving the policy's goals.